Leaf geometric morphometrics among populations of Dalbergia ecastaphyllum (L.) Taub. - Daniel Vieira de Morais; Lorena Andrade Nunes; Vandira Pereira da Mata; Maria Angélica Pereira de Carvalho Costa; Geni da Silva Sodré; Carlos Alfredo Lopes de Carvalho (Bioscience Journal, 2019)
Leaves are plant structures that express important traits of the environment where they live. Leaf description has allowed identification of plant species as well as investigation of abiotic factors effects on their development, such as gases, light, temperature, and herbivory. This study described populations of Dalbergia ecastaphyllum through leaf geometric morphometrics in Brazil. We evaluated 200 leaves from four populations. The principal component analysis (PCA) showed that the first four principal components were responsible for 97.81% of variation. The non-parametric multivariate analysis of variance (NPMANOVA) indicated significant difference between samples (p = 0.0001). The Mentel test showed no correlation between geographical distances and shape. The canonical variate analysis (CVA) indicated that the first two variables were responsible for 96.77 % of total variation, while the cross-validation test showed an average of 83.33%. D. ecastaphyllum leaves are elliptical and ovate.